Endocrine therapy for breast cancer: a model of hormonal manipulation - Johnston, Simon J.; Cheung, Kwok-Leung (Springer, 2018)
Oestrogen receptor (ER) is the driving transcription factor in 70% of breast cancer. Endocrine therapies targeting the ER represent one of the most successful anticancer strategies to date. In the clinic, novel targeted agents are now being exploited in combination with established endocrine therapies to maximise efficacy. However, clinicians must balance this gain against the risk to patients of increased side effects with combination therapies. This article provides a succinct outline of the principles of hormonal manipulation in breast cancer, alongside the key evidence that underpins current clinical practice. As the role of endocrine therapy in breast cancer continues to expand, the challenge is to interpret the data and select the optimal strategy for a given clinical scenario.